Zbigniew Rau, Contractrianism versus holism. Reinterpreting Locke’s Two Treatises of Government, University Press of America, Inc., Lanham, New York, London 1995, ss. 152. - Maria Zmierczak (Czasopismo Prawno-Historyczne, 1996)
Recenzja: Z. Rau, Contractrianism versus holism. Reinterpreting Locke’s Two Treatises of Government, University Press of America, Inc., Lanham, New York, London 1995, ss. 152.